2018
DOI: 10.3389/fonc.2018.00081
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Symbiosis and Immunomodulation: How Tumor Cell-Derived Lactate May Disturb Innate and Adaptive Immune Responses

Abstract: The tumor microenvironment (TME) is composed by cellular and non-cellular components. Examples include the following: (i) bone marrow-derived inflammatory cells, (ii) fibroblasts, (iii) blood vessels, (iv) immune cells, and (v) extracellular matrix components. In most cases, this combination of components may result in an inhospitable environment, in which a significant retrenchment in nutrients and oxygen considerably disturbs cell metabolism. Cancer cells are characterized by an enhanced uptake and utilizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
75
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 154 publications
0
75
0
1
Order By: Relevance
“…Tumour microenvironment conditioning through reduced lactate export is likely to be the main mechanism for the increased tumour immune cell infiltration given the known inhibitory effects of lactate on anti-tumour immune cell activity and expansion, and the lack of effect on spleen immune cell phenotype. [34][35][36] Interestingly, our human PBMC data also show that AZD3965 inhibits MCT1 in immune cells themselves potentially modulating their metabolism and also their activity. 37 In agreement with this observation, previous work has shown that MCT1 inhibition has an immunosuppressive effect on T cells, preventing their expansion upon activation.…”
Section: Discussionmentioning
confidence: 55%
“…Tumour microenvironment conditioning through reduced lactate export is likely to be the main mechanism for the increased tumour immune cell infiltration given the known inhibitory effects of lactate on anti-tumour immune cell activity and expansion, and the lack of effect on spleen immune cell phenotype. [34][35][36] Interestingly, our human PBMC data also show that AZD3965 inhibits MCT1 in immune cells themselves potentially modulating their metabolism and also their activity. 37 In agreement with this observation, previous work has shown that MCT1 inhibition has an immunosuppressive effect on T cells, preventing their expansion upon activation.…”
Section: Discussionmentioning
confidence: 55%
“…Cervical cancer is caused by persistent infection with high oncogenic risk HPV types and has been shown to express MCTs,20 indicating lactate secretion. Many solid tumors display glycolytic metabolism and secrete lactate, leading to suppression of antitumor responses 44. Our results show that cervical cancer cell lines secrete lactate and that this molecule can be detected in the plasma of patients with cervical lesions and cervical cancer.…”
mentioning
confidence: 61%
“…Cervical cancer is caused by persistent infection with high oncogenic risk HPV types and has been shown to express MCTs, indicating lactate secretion. Many solid tumors display glycolytic metabolism and secrete lactate, leading to suppression of antitumor responses …”
Section: Discussionmentioning
confidence: 99%
“…Beyond the effects on cell proliferation, tumor cell-derived lactate produced during aerobic glycolysis has a profound effect on the tumor microenvironment and cancer progression [34]. Extracellular lactate has deleterious effects on infiltrating T-cells, while serving as a nutrient source for immunosuppressive tumor-associated macrophages [34][35][36]. pRb-deficient tumors exhibited increased lactate production from glucose ( Figure 3F), yet whether this influences the immune response in the TME remains unclear.…”
Section: Discussionmentioning
confidence: 99%